Risk factors and their negative impact on the formation reproductive function (Overview) - Kholova Nodira Fazliddinovna (Genius Publishing Group, 2022)
The identification of risk factors and the prediction of disorders of the reproductive health of adolescent girls, the development of a modern strategy for the formation of reproductive potential by strengthening the preventive focus is an actual practical area of national health care.
Keywords: reproductive health; teenage girls; health maiden